Supervision Model of Supervisors of Islamic Religious Education in Improving The Personal and Social Competence of PAI Teachers in Wadaslitang District - Salis Irvan Fuadi; Robingun Suyud El Syam; Anggitiyas Sekarinasih; Hendri Purbo Waseso (Program Pascasarjana Pendidikan Islam Universitas Islam Darul Ulum Lamongan, 2023)
This study seeks to reveal how the implementation of the PAI supervisory supervision model in improving the personality and social competence of PAI teachers in the Wadaslintang District. This research is a qualitative type, using a descriptive explanatory case study strategy. The subjects used samples with several data sources from school principals, PAI supervisors and PAI teachers in Wadaslintang District, and structured interview data collection techniques, questionnaires or questionnaires, and documentation. After being analyzed, it was written that in choosing the model for the PAI supervisor in the Wadaslintang sub-district, they did not use certain analytical techniques, they simply chose the preferred model and adjusted it to the conditions of the teacher where the PAI teacher was in the Wadaslintang sub-district. Seeing the habits of PAI teachers in the Wadaslintang sub-district who are compact and considerate of the conditions of other people, especially fellow teachers, so that supervisors use artistic models. According to the artistic approach, the supervisor knows about learning and is experienced as a teacher so that the person concerned gives meaning to ongoing learning without deviating from it. Supervisor approach with several steps: (1) Does not provide information about the learning to be observed. (2) Observing teachers who are teaching; (3) Observations that are carried out thoroughly from the beginning to the end of learning; (4) Provide a formal interpretation of the results of observations; (5) Submission of teaching interpretation results to teachers both in writing and orally.